2005: LAS2005: Critiquing and Reflecting: LAS Profession and Practice: Refereed Proceedings of the 2005 Biannual Language and Academic Skills in Higher Education Conference, Australian National University Canberra, 24-25 November 2005 - Milnes (Editor), Stephen (Journal of Academic Language and Learning, 2026)
Formatting note: In the pdf, an article can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. Preface … 7-10 The John Grierson Keynote: Critiquing and reflecting: Kate Chanock … 11–19 Language and academic skills advising in the era of internationalisation: A multiliteracies perspective: Adela Abu-Arab … 21–29 LAS advisers as virtual tutors: A report on an interactive online writing course for undergraduate students: Chi Baik and Damian Sweeney … 31–43 ‘Knowingly constructing’ our future: Reflecting on individual LAS practice: Annie Bartlett … 45–54 The LAS adviser’s role in supporting dyslexic students: Kate Chanock … 55–64 Creativity versus routinisation: Critical reflections on the role of the learning adviser: Susan Crozier … 65–73 Toward a knowledge management framework for language and learning services: Brian Curtis … 75–85 Locating learning advisers in the new university: What should be our role? Wendy Green, Sara Hammer and Robyn Stephens … 87–98 Improving oral communication in pharmacy education through interdisciplinary research: Bev Kokkinn and Libby Hotham … 99–108 Postgraduate Essentials: An online transition program for commencing PhD students: Wendy Larcombe and Anthony McCosker … 109–118 LAS and its disciplinary ambitions: Stephen Milnes … 119–129 Theorising what we do: Defamiliarise the university: Kerry O’Regan … 131–139 Representation for (re)invention: Alisa Percy and Jeannette Stirling … 141–154 A web of interconnectedness: The implications of coordinating a peer mentoring program: Clare Power and Neera Handa … 155–165 Should students acknowledge significant learning assistance with their assignments or theses? David R. Rowland and Mandy Symons … 166–176 Truth games / Truth claims: Resisting institutional notions of LAS as remediation: Jeannette Stirling and Alisa Percy … 177–187 Embedded information literacy: A collaborative approach: D. Ambery and J. Manners … 188–204 Email in a ‘thirdspace’: enhancing intercultural communication: Helen Benzie … 205-216 Creating a Rich Environment: Cooperation between academic support and disciplinary teaching staff: Glenda Crosling and Anne V. Wilson … 217–231 Making a difference and self-efficacy: Interviews with Jude Carroll, Kate Chanock and Marcia Devlin: Julianne East … 232–247 Leadership in LAS: Beginning a conversation: Liz Horrocks … 248–259 The poetics of writing instruction: Andrew Johnson … 260–270 Learning and the Net Generation: Are LAS advisers helping or hindering? Alex McNight … 271–284 The perils of skills: Towards a model of integrating graduate attributes into the Disciplines: Tim Moore and Brett Hough … 285–302 Chasing Pokemon – in pursuit of the LAS ideal: Chris Orsmond … 303–323 Who am I writing for? Potential and problems of writer roles in assessment tasks: Jan Pinder … 324–333 Role conflation in the writing of undergraduate Law students: Steve Price … 334–346 While they were learning, what was I doing? Anne V. Wilson … 347–358